A photoinduced shape memory composite material and its preparation method and application
By using bio-based materials such as polylactic acid, epoxidized natural rubber and marine biotoon, composite materials with high toughness and photometric shape memory performance are prepared, which solves the problems of limited application range and insufficient mechanical properties of thermal shape memory materials in the prior art, and achieves the development of materials with excellent shape memory performance under the premise of sustainable development.
Patent Information
- Application Number
- CN202310221346.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-09
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2043-03-09
AI Technical Summary
Existing shape memory materials based on thermoplastic vulcanized glue are mainly heat-induced, with limited application range, and the introduction of functional fillers may lead to deterioration of the mechanical properties of the matrix, and the combination of high toughness and photometric shape memory properties has not yet been achieved.
Using bio-based renewable resources such as polylactic acid, epoxidized natural rubber and marine biotoon, composite materials with high toughness and photoreal shape memory properties are prepared through kneading and melt blending processes.
It realizes the high toughness and excellent photothermal effect of composite materials, has shape memory performance triggered by near-infrared light, and meets the requirements of sustainable development.
Smart Images

Figure BDA0004116789650000021 
Figure BDA0004116789650000022 
Figure BDA0004116789650000041
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer materials technology, and in particular to a photoinduced shape memory composite material, its preparation method, and its application. Background Technology
[0002] With the global goals of peak carbon emissions and carbon neutrality being set, bio-based materials, represented by polylactic acid (PLA), are receiving increasing attention. Bio-based thermoplastic vulcanizates (TVRs), prepared primarily from PLA and epoxidized natural rubber (ENR), offer advantages such as readily available and renewable raw materials, shape memory properties and easy programming, simple manufacturing processes, and good product performance. To protect the environment and promote sustainable development, researchers have invented shape memory materials based on TVRs, which have broad application potential in fields such as biomedicine.
[0003] Shape memory polymers can be induced by various mechanisms, such as heat, magnetism, light, and humidity. However, current shape memory materials based on thermoplastic vulcanizates are mostly thermally induced, limiting their application range. While introducing functional fillers can impart responsiveness to different stimuli, this may also lead to a deterioration of the matrix's mechanical properties. Chinese invention patent CN109878070A discloses a method for preparing a 3D-printed thermotropic shape memory polylactic acid (PLA) composite material. This method involves physically blending polycaprolactone-modified materials into a PLA matrix, lowering the glass transition temperature to prepare the 3D-printed PLA-based composite material, which exhibits thermotropic shape memory properties. However, this method only achieves the thermotropic shape memory properties of the composite material through simple blending, resulting in a single stimuli and requiring contact with a heat source. Furthermore, the material's basic properties are poor, and the toughness and functionality of the PLA-based material have not been designed, further limiting its application areas.
[0004] Therefore, it is necessary to develop a new shape memory composite material that possesses high toughness and photo-induced shape memory properties. Summary of the Invention
[0005] The present invention aims to at least solve one of the technical problems existing in the prior art. To this end, the first aspect of the present invention proposes a photo-induced shape memory composite material with high toughness and photo-induced shape memory properties.
[0006] A second aspect of the present invention also provides a method for preparing a photo-induced shape memory composite material.
[0007] A third aspect of the present invention also provides an application of photo-induced shape memory composite materials.
[0008] A photo-induced shape memory composite material according to a first aspect embodiment of the present invention comprises the following components in parts by weight:
[0009]
[0010]
[0011] The photo-induced shape memory composite material according to embodiments of the present invention has at least the following beneficial effects:
[0012] The polylactic acid and epoxidized natural rubber used in this invention have a large viscosity difference. The cross-linked epoxidized natural rubber phase is distributed in a continuous network structure in the polylactic acid matrix, which makes the composite material have a quasi-bicontinuous phase structure. This structure gives the thermoplastic vulcanizate a good shape memory effect.
[0013] The photo-induced shape memory composite material of the present invention has high toughness. It is obtained by mixing marine biological toner with epoxidized natural rubber to obtain a compound, and the epoxidized natural rubber is reinforced by marine biological toner nanoparticles. The toughness of polylactic acid matrix is improved by reinforcing the rubber phase.
[0014] The composite material of this invention possesses photo-induced shape memory properties. By introducing marine bio-toner into a thermoplastic vulcanizate, the composite material is not only toughened but also exhibits excellent photothermal effects, thereby enabling the composite material to achieve shape memory properties induced by near-infrared light.
[0015] The raw materials of the photo-induced shape memory composite material of this invention are polylactic acid, epoxidized natural rubber, marine biological toner and phytic acid, all of which are bio-based renewable resources, which do not pollute the environment and meet the requirements of sustainable development.
[0016] According to some embodiments of the present invention, the photo-induced shape memory composite material comprises the following components in parts by weight:
[0017]
[0018] Therefore, within the aforementioned range, it exhibits better toughness and photo-induced shape recovery properties.
[0019] According to some embodiments of the present invention, the average particle size of the marine bio-toner is 10–1000 nm. According to some embodiments of the present invention, the average particle size of the marine bio-toner is 100–500 nm. According to some embodiments of the present invention, the average particle size of the marine bio-toner is 10 nm, 100 nm, 200 nm, 300 nm, 500 nm, 700 nm, 800 nm, 1000 nm, or within a range consisting of any two of the above values. Therefore, the toughening effect is better.
[0020] According to some embodiments of the present invention, the marine organisms in the marine biological toner are selected from at least one of octopus and squid.
[0021] According to some embodiments of the present invention, the marine biological toner is obtained by grinding the ink sac of a marine organism.
[0022] According to some embodiments of the present invention, the number average molecular weight of the polylactic acid is 20,000 to 200,000.
[0023] According to some embodiments of the present invention, the polylactic acid includes at least one of poly-D-lactic acid, poly-L-lactic acid, or racemic polylactic acid.
[0024] According to some embodiments of the present invention, the polylactic acid is dried before use, preferably at a temperature of 60–100°C.
[0025] According to some embodiments of the present invention, the degree of epoxidation of the epoxidized natural rubber is 10 mol% to 75 mol%. According to some embodiments of the present invention, the degree of epoxidation of the epoxidized natural rubber is 25 mol% to 50 mol%. According to some embodiments of the present invention, the degree of epoxidation of the epoxidized natural rubber is 10 mol%, 25 mol%, 40 mol%, 50 mol%, 60 mol%, 75 mol%, or within a range consisting of any two of the above values.
[0026] According to a second aspect of the present invention, a method for preparing the above-described photoinduced shape memory composite material is provided, comprising the following steps:
[0027] S1. Mix marine biological toner with epoxidized natural rubber evenly to obtain a compound;
[0028] S2. Polylactic acid is melted for the first time, and then mixed with compound rubber and phytic acid for a second melt blending to obtain photo-induced shape memory composite material.
[0029] The method for preparing photo-induced shape memory composite materials according to embodiments of the present invention has at least the following beneficial effects:
[0030] This invention first pre-mixes marine biological toner with epoxidized natural rubber, then melt-blends polylactic acid with the mixed rubber, and then adds phytic acid to cause dynamic vulcanization of the epoxidized natural rubber under the action of phytic acid, finally obtaining a photo-induced shape memory composite material with high toughness.
[0031] According to some embodiments of the present invention, the addition of phytic acid also has an antioxidant effect.
[0032] According to some embodiments of the present invention, in step S2, the temperatures of the first melting and the second melting are 150 to 200°C.
[0033] According to some embodiments of the present invention, the melt blending time is 1 to 20 minutes.
[0034] The third aspect of this invention provides the application of the above-described photodeformation composite material in biomedicine and flexible wearable products.
[0035] Other features and advantages of the invention will be set forth in the description which follows, and will be apparent in part from the description, or may be learned by practicing the invention. Detailed Implementation
[0036] The following are specific embodiments of the present invention, and the technical solutions of the present invention will be further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.
[0037] Unless otherwise specified, the reagents, methods and equipment used in this invention are all conventional reagents, methods and equipment in this technical field.
[0038] The polylactic acid (Hisun, REVODE 110) in the examples and comparative examples was dried in an 80°C drying oven for 8 hours before use;
[0039] Epoxidized natural rubber A: epoxidation degree 50 mol%; purchased from the Chinese Academy of Tropical Agricultural Sciences;
[0040] Epoxidized natural rubber B: epoxidation degree 25 mol%; purchased from the Chinese Academy of Tropical Agricultural Sciences;
[0041] Marine biological toner: Black clumps of squid toner nanoparticles were taken from commercially available fresh squid sacs. The crude product was added to deionized water and mechanically stirred, ultrasonically dispersed, and centrifuged at high speed to obtain squid ink nanoparticles. The above steps were repeated 5 times, and the resulting product was ground to obtain squid ink nanoparticles with a particle size of 150nm.
[0042] Example 1
[0043] Example 1 provides a photo-induced shape memory composite material, comprising the following components in parts by weight:
[0044]
[0045] The preparation method includes the following steps: S1, mixing marine biological toner with epoxidized natural rubber A on a two-roll mill to obtain a compound;
[0046] S2. Polylactic acid was added to a torque rheometer at 170°C and 60 rpm and melted for 3 minutes. Then, the compound was added and phytic acid was added for melt blending for 5 minutes to initiate dynamic vulcanization, thus obtaining a photo-induced shape memory composite material.
[0047] Examples 2-7
[0048] Examples 2-7 provide a series of photo-induced shape memory composite materials, the component contents of which are shown in Table 1, and the preparation method is the same as in Example 1.
[0049] Table 1
[0050]
[0051] Examples 8-13
[0052] Examples 8-13 provide a series of photo-induced shape memory composite materials, the component contents of which are shown in Table 2, and the preparation method is the same as in Example 1.
[0053] Table 2
[0054]
[0055]
[0056] Example 14
[0057] Example 14 provides a photo-induced shape memory composite material, the composition content and preparation method of which are basically the same as those in Example 1, except that the epoxidized natural rubber is epoxidized natural rubber B.
[0058] Comparative Examples 1-5
[0059] Comparative Examples 1-5 provide a series of photo-induced shape memory composite materials, the preparation methods of which are basically the same as those in Example 1, and the component contents are shown in Table 3.
[0060] Table 3
[0061] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Polylactic acid 100 80 80 10 90 Epoxidized Natural Rubber A —— 20 20 90 10 Marine biological toner 50 50 —— 50 50 Phytic acid 2 —— 2 2 2
[0062] Performance testing
[0063] Mechanical and shape memory properties were tested on the samples. The comparative and example samples were all processed as follows: the samples were crushed and then injection molded to obtain test strips. The injection molding conditions were: feeding section 165°C, compression section 170°C, homogenization section 170°C, die head and die section 175°C, and screw speed 90 rpm.
[0064] Mechanical performance testing
[0065] According to the national standard GB / T 1040.1-2006, the tensile properties of all samples were measured using a universal testing machine (INSTRON 5966) at 25℃ and a tensile speed of 50 mm / min. Five samples were tested for each measurement, and the average value was taken. The notched impact strength of the samples was tested according to GB / T1843-2008. The sample thickness was 4 mm, the notch type was A, and the pendulum weight was 5.5 J. Five samples were tested for each measurement, and the average value was taken. For unbroken specimens, the final notched impact strength value was calculated proportionally based on the remaining length.
[0066] Shape memory performance test
[0067] The thermally induced shape memory properties of composite materials were tested using a high-low temperature tensile testing machine. The specific process is as follows: (1) Draw a line segment L0 with a length of 20 mm in the middle area of the dumbbell-shaped sample (thickness of 1 mm); (2) Place the sample at 70℃ for 5 min to ensure uniform heating, and then deform it at a rate of 5 cm / min to 100% strain. Immediately pass liquid nitrogen to cool the experimental chamber. Keep the load constant during the cooling process. When the temperature drops to 25℃, measure the distance L1 between the two ends; (3) Unload the sample and leave it at room temperature. After 24 h, record the length L2 between the two ends; (4) Place the sample in a 70℃ oven and heat it for 5 min to allow the sample to recover its shape. Then record the length L3 between the two ends of the sample. The shape fixation rate (R) of the composite material can be calculated by formulas (1) and (2). f ) and shape recovery rate (R r ):
[0068] R f = (L2-L0 / L1-L0)×100% (1)
[0069] R r =(L2-L3 / L2-L0)×100% (2)
[0070] The photoinduced shape memory properties of the composite material were measured under near-infrared laser irradiation. First, a rectangular strip measuring 40mm × 10mm × 1.0mm was folded into a "U" shape at 70℃ and cooled to fix the shape. Then, the strip was irradiated with a near-infrared laser, and the shape recovery process of the composite material under near-infrared light was recorded using a digital camera. The residual angle (θ) after shape recovery was recorded. r And the photo-induced shape recovery rate (R) of the composite material was calculated according to formula (3). r1 ) See Table 4 for specific data.
[0071] R r1 =(θ r (180°) × 100%
[0072] Table 4
[0073]
[0074]
[0075] As shown in Table 3, Examples 1-7, 10, 13, and 14 exhibit super-toughness, with none of the specimens completely broken during the notched impact test. Table 4 shows that the addition of epoxidized natural rubber (Comparative Example 3) improves the toughness of PLA and also significantly enhances its shape recovery. The addition of squid ink further enhances the toughness of the composite material. Examples 1-7 demonstrate that the addition of squid ink and epoxidized natural rubber synergistically toughens PLA, resulting in a thermoplastic vulcanizate with super-toughness.
[0076] As shown in Table 4, the addition of squid ink effectively improved the shape recovery of PLA / ENR thermoplastic vulcanizates, increasing the shape recovery rate to over 97% as in Examples 1-7. Simultaneously, squid ink exhibits excellent photothermal effects, converting light energy into heat energy under near-infrared light irradiation, thus endowing the composite material with superior photo-induced shape memory properties. Examples 1, 9, and 10 demonstrate that the addition of an appropriate amount of squid ink enabled the thermoplastic vulcanizates to achieve a shape recovery rate of over 91% under light stimulation.
[0077] Comparative Examples 1 through 5 show that Comparative Example 1, which did not contain epoxidized natural rubber, had an extremely low notched impact strength of only 3.1 kJ / m. 2 Comparative Example 2 did not include phytic acid, resulting in the composite material not undergoing dynamic vulcanization, thus reducing its overall performance. Comparative Example 3 did not include marine bio-toner, leading to a decrease in its notched impact strength and the absence of photo-induced shape recovery. Comparative Examples 4 and 5 used polylactic acid and epoxidized natural rubber, which are outside the scope of this invention. Comparative Example 4 exhibited low tensile strength and shape retention, while Comparative Example 5 also showed a decrease in notched impact strength.
[0078] The present invention has been described in detail above with reference to the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention.
Claims
1. A light-induced shape memory composite material, characterized in that: The composition comprises the following components calculated by weight: The marine organism in the marine organism ink powder is selected from at least one of octopus and squid.
2. The photoinduced shape memory composite material according to claim 1, characterized in that: The composition comprises the following components calculated by weight:
3. The photoinduced shape memory composite material according to claim 1, characterized in that: The average particle size of the marine biological toner is 10 to 1000 nm.
4. The photoinduced shape memory composite material according to claim 3, characterized in that: The average particle size of the marine biological toner is 100-500nm.
5. The photoinduced shape memory composite material according to claim 1, characterized in that: The number average molecular weight of the polylactic acid is 20,000 to 200,000.
6. The photoinduced shape memory composite material according to claim 1, characterized in that: The polylactic acid includes at least one of poly D-lactic acid, poly L-lactic acid or racemic polylactic acid.
7. The photoinduced shape memory composite material according to claim 1, characterized in that: The epoxidation degree of the epoxidized natural rubber is 10 mol% to 75 mol%.
8. The method for preparing the photoinduced shape memory composite material according to any one of claims 1 to 7, characterized in that: The steps include: S1, mixing the marine biological toner and the epoxidized natural rubber to obtain a mixed rubber; S2, melting the polylactic acid for the first time, adding the compound rubber and phytic acid for the second melting and blending, so as to obtain a photoinduced shape memory composite material.
9. The method for preparing the photoinduced shape memory composite material according to claim 8, characterized in that: In step S2, the temperature of the first melting and the second melting is 150-200°C.
10. Use of the photoinduced shape memory composite material according to any one of claims 1 to 7 in biomedical and flexible wearable products.
Citation Information
Patent Citations
Preparation method of 3D printing thermotropic shape memory polylactic acid composite material
CN109878070A
Bio-based thermoplastic elastomer with shape memory function and preparation method thereof
CN105038165A
Polylactic acid with enhanced toughness and strength and preparation method and application thereof
CN107022181A